The Value Relevance of Fair Value on Non-Financial Asset - Ananta D. Pratiwi; Frida M. Sumual; Linda A.O Tanor (Journal of International Conference Proceedings (JICP), 2022)
Accounting information is presented in financial statements as one of the information that investors need to make the best judgment. The reaction of investors to the release of accounting information indicates the degree of value relevance of accounting information. This study aimed to examine the value relevance of accounting information through earnings, book value of equity, and fair value on non-financial assets. This study used 21 LQ45 Index companies listed on the Indonesia Stock Exchange (IDX) from 2018-2021. Multiple linear regression was used as an analytical tool to test the relationship between research variables. The results showed that earnings and book value of equity had positive effect on stock price and thus had value relevance. The fair value on non-financial assets was found to have a negative effect on stock price and thus had no value relevance. This study provides empirical evidence that earnings and book value of equity are useful information for investors in decision making.Keywords: Book Value of Equity; Earnings; Fair Value; Non-financial Assets; Value Relevance